ASSESSMENT OF IMPACT OF PARTHENIUM HYSTEROPHORUS THENIUM HYSTEROPHORUS L. ON EISENIA FOETIDA THROUGH VERMICOMPOSTING - BHARTI SINGH RAIPAT (The Bioscan, 2010)
The paper deals with the impact of Parthenium hyterophorus on the eartheworm Eisenia foetida during vermicomposting. Various combinations of Parthenium and cow dung as well as long gress were used. Different parameters earthworm population like increase in population, population growth rate, biomass, age class were analysed following standard methods. The combination with parthenium always showed adverse impact .